Outcomes of nonoperative management of splenic injury: A retrospective cohort from a level 1 trauma center in Thailand - Naruthep Nuchaikaew; Osaree Akaraborworn; Teeravut Tubtawee; Burapat Sangthong; Komet Thongkhao (Archives of Trauma Research, 2022)
Background and Objectives: Nonoperative management (NOM) of splenic injury is the standard treatment for all splenic injury patients who are hemodynamically stable. However, it may be a challenge in developing countries with limited intensive care resources. This study aimed to review the outcomes and identify the factors of unsuccessful NOM of splenic injury in a Level 1 trauma center in Thailand. Materials and Methods: This was a retrospective review that collected data from the trauma registry. The enrolled patients had a splenic injury and underwent NOM from 2009 to 2016. Failure of NOM was defined as the need for an operation on the spleen after NOM. The outcomes of NOM were described, and the predictors for failure of NOM were identified. Results: Seventy-two splenic injury patients were included in the study. The majority of patients were involved in a motorcycle crash (56%). The average injury severity score was 20. Fifty-nine patients (89%) were successfully treated as NOM. Six patients underwent embolization (8%), and none of the patients required operative management. Univariate analysis showed that hemoperitoneum in ≥4 regions (odds ratio [OR] 3.96, 95% confidence interval [CI] 0.79–25.53; (P = 0.05) and received packed red cells >2 units within 24 h (OR 20, 95% CI 2.15–242; P = 0.003) were significantly associated with failure of NOM. Conclusions: NOM of splenic injury can be performed successfully in a trauma center in a developing country. Splenic angioembolization might be helpful to increase the success rate. The amount of hemoperitoneum was a significant predictor of failed NOM.